HLA and sexually transmitted diseases in prostitutes. Issue 3 (June 1979) - Chan, S H; Tan, T; Kamarudin, A; Wee, G B; Rajan, V S
Abstract : The HLA profile of 148 unrelated, Chinese prostitutes (56 with repeated gonococcal infection, 31 with syphilis, 31 with gonorrhoea and syphilis, and 30 with no evidence of infection) was compared with that of 238 unrelated, healthy, Chinese control subjects. The joint occurrence of AW19 B17 was observed in 25.8% of prostitutes with double infections compared with 6.7% of control subjects, while that of A11 B15, on the other hand, was associated with a resistance to syphilis and gonorrhoea. The latter profile was observed in 46.7% of prostitutes in business for more than two years who were resistant to disease, in 30% of prostitutes with an overall disease resistance, in 13.4% of control subjects, and in only 3.2% of prostitutes with combined syphilis and gonorrhoea. Because of the statistical uncertainty when multiple variables are being analysed these studies should be repeated in other groups of prostitutes of the same and different ethnic origins.